When and how to create a job: The survival of new jobs in Austrian firms - René Böheim; Alfred Stiglbauer; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2005)
While the volatility of job creations has been studied extensively, the survival chances of new jobs are less researched. The question when and how to expand a firm is of importance, both from the firm's and from a macro perspective. Adjustment cost theories and arguments about option values of investment in firm expansion make predictions about the timing, sequencing and form of firm expansions. When we analyze 21 years of job creation in Austria, we find that the survival of new jobs (and of new firms) depends upon the state of the business cycle at the time of job creation, on the number of jobs created, and on firm age. Jobs in new firms last longer than new jobs in continuing firms.
Keywords: J23; J63; E24; E32; 330; job creation; business cycle; reallocation; persistence; Arbeitsnachfrage; Personalplanung; Kündigung; Konjunktur; Österreich